All-inkjet-printed flexible ZnO micro photodetector for a wearable UV monitoring device. (30th January 2017) - Tran, Van-Thai; Wei, Yuefan; Yang, Hongyi; Zhan, Zhaoyao; Du, Hejun
Abstract: Fabrication of small-sized patterns of inorganic semiconductor onto flexible substrates is a major concern when manufacturing wearable devices for measuring either biometric or environmental parameters. In this study, micro-sized flexible ZnO UV photodetectors have been thoroughly prepared by a facile inkjet printing technology and followed with heat treatments. A simple ink recipe of zinc acetate precursor solution was investigated. It is found that the substrate temperature during zinc precursor ink depositing has significant effects on ZnO pattern shape, film morphology, and crystallization. The device fabricated from the additive manufacturing approach has good bendability, Ohmic contact, short response time as low as 0.3 s, and high on/off ratio of 3525. We observed the sensor's dependence of response/decay time by the illuminating UV light intensity. The whole process is based on additive manufacturing which has many benefits such as rapid prototyping, saving material, being environmentally friendly, and being capable of creating high-resolution patterns. In addition, this method can be applied to flexible substrates, which makes the device more applicable for applications requiring flexibility such as wearable devices. The proposed all-inkjet-printing approach for a micro-sized ZnO UV photodetector would significantly simplify the fabrication process of micro-sized inorganic semiconductor-based devices. A potential application is real-time monitoring of UV light exposure to warn users about unsafe direct sunlight to implement suitable avoidance solutions.